On the Cost-Benefit Tradeoffs of Cloud Storage Services for End Users and Service Providers - Gonçalves, Glauber; Vieira, Alex; Almeida, Jussara (Anais Estendidos do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2018: Anais Estendidos do XXXVI Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc_estendido.2018.14186, 2018)
Cloud Storage is a very popular Internet service. It allows users to backup data to the cloud as well as to perform collaborative work while sharing content. Despite the increasing interest in cloud storage, a thorough investigation on the costs and beneﬁts of this service for providers and end users has not been conducted yet. This dissertation aims at investigating such cost-beneﬁt tradeoffs for both providers and end users jointly. Using data collected from a real service (Dropbox), we developed new models, methodologies and tools to support providers and users in improving jointly their beneﬁts in cloud storage.